Adolescents with Cystic Fibrosis Expressing their Possible Selves through Photovoice: A Longitudinal Interpretative Phenomenological Analysis to Prepare a Peer Support Intervention for Healthcare Transition - Maxime Morsa; Adélaïde Vincent-Lardy; Julie Haesebaert; Catherine Llerena; Lucie Pelz; Philippe Reix; Rémi Gagnayre; Quitterie Reynaud (Patient Experience Journal)
While the transition from pediatric to adult care has become a field of study and practice focused on preparing the adolescent to ``become an adult with a chronic condition'', we are conducting participatory research to develop, implement, and evaluate a peer-support intervention aimed at supporting transition from pediatric to adult care for adolescents living with cystic fibrosis within two hospital centers in France. In preparation for this intervention, we would like to better understand how peer support could support identity self-determination of the adolescents. We conducted a longitudinal qualitative research using photovoice technique. For one year, 8 French adolescents (15–18 years old) with cystic fibrosis were interviewed 3 times (every 6 months) and, based on a photo representing what ``becoming an adult'' meant to them and that they had taken, they explained their experience of transitioning to adulthood. Data were analyzed using the interpretative phenomenological analysis approach. The evolution of adolescents' capacities to integrate disease into their identity and imagine possible selves that are not determined by the disease varies depending on a range of exploratory processes and self-event connections that we mapped to produce a dynamic framework of ``illness identity'' development. Rejecting master narratives of illness identity, adolescents seek to develop a self-determined gaze, mobilizing cultural and social mediation in particular. In this sense, peer support intervention could support the adolescent's agentivity.